Implementasi Kebijakan Sertifikasi Guru PAI dan Implikasinya Pada Proses Pembelajaran di SMAN 1 Baitussalam Aceh Besar - Putri Nur Faizah; Silahuddin; Zulfatmi Budiman (Al-Mudarris, 2026)
This study aims to analyze the implementation of the certification policy for Islamic Religious Education Teachers (PAI), policies from schools in supporting the implementation of PAI teacher certification, its implications for the learning process, and the obstacles faced by PAI teachers in participating in the implementation of certification. Certification is a policy from the government to improve the professionalism of educators. However, the effectiveness of its implementation is not only determined by national regulatory policies, but also how schools as policy implementers support the implementation. This research uses a qualitative-descriptive method, with data collection techniques in the form of in-depth interviews, observations, and documentation. The informants from this study consist of PAI teachers who have participated in certification through the PLPG and PPG routes. The results of the study showed that certification had a positive impact on improving the pedagogical, professional, social, and personality competencies of PAI teachers. Professional allowances also increase teachers' motivation and welfare so as to support media development, learning creativity, and the use of technology in the teaching and learning process. The implementation of certification is effective because of the school's support through the provision of facilities, supervision of the principal, and the fulfillment of teaching hours. However, there are several obstacles, such as the heterogeneity of student character and the uneven post-certification coaching policy. This research confirms that the success of teacher certification is not only determined by national policies, but also by internal school policies that strengthen its implementation. These findings are expected to be a reference for schools, governments, and policy makers in strengthening the implementation of teacher certification in a sustainable manner.